Ischemic stroke in children: a study of the associated alterations - Ranzan,Josiane (2004)
Arterial ischemic stroke (AIS) in children is a relatively rare disease, not yet clearly understood and with a multifactored etiology. It can cause a severe impact on the child and be the first manifestation of a systemic disease. Delayed diagnosis is still common and research on the subject in our field practically does not exist. Prothrombotic disorders have been described as important causative factors of the ischemic event in children. Forty-six patients from zero to 18 years of age diagnosed with AIS were studied in the period between March 2002 and September 2003. Laboratory tests were realised including coagulation proteins and echocardiogram. AIS of the newborn occurred in 37% of the cases. Focal seizures and hemiparesis were the most frequent symptoms; 40% of the patients presented prior pathologies. Abnormalities of the S and C proteins occurred in 22% and 17%. Associated alterations, particularly those that generate a hypercoagulability state, indicate more than one risk factor for this disease in childhood.